KONSEP KOTA KOMPAK DALAM KAMPUNG TRADISIONAL KAUMAN SEMARANG - Hafidzah, Asri Amalia; Sudarwanto, Budi (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: If the compact city concept is a modernization of the city concept, therefore in the context of a traditional city that has been developed for centuries could be claimed to have the opposite concept. This study is going to explain that the compact city concept can be found in the traditional city. The purpose of this study is to identify the traditional Kauman village which is a heritage village, according to the compact city aspects, using descriptive qualitative method within the Kauman heritage area of Semarang. The results of this study show that Kauman, when measured using a compact city assessment according to Lim's Theory, has met several criteria even though it is still in the form of a traditional village. However, in terms of mobility and accessibility, Kauman has not met the qualifications. It turns out that cities that have been built traditionally, in their development have adopted several sustainable compact city concepts in their own way in terms of sustainability and maintenance of the village as a heritage area.Abstrak: Jika konsep kota kompak adalah gagasan modernisasi pada konsep kota, maka dalam konteks kota tradisional yang sudah berkembang dalam hitungan abad, konsep ini dapat dikatakan berlawanan. Penelitian ini akan mengkaji tentang bagaimana konsep kota kompak ditemukan dalam kota tradisional. Tujuan dari penelitian ini adalah untuk mengidentifikasi kampung tradisional Kauman yang merupakan kampung heritage, terhadap aspek-aspek yang ada dalam kota kompak, menggunakan metode kualitatif deskriptif di lingkup wilayah heritage Kauman Semarang. Hasil penelitian ini menunjukan bahwa Kauman, jika diukur menggunakan penilaian kota kompak menurut Teori Lim, sudah memenuhi beberapa kriteria walaupun masih dalam bentuk kampung tradisional. Namun dalam aspek mobilitas dan aksesibilitas, Kauman belum memenuhi kualifikasi. Ternyata kota yang dibangun secara tradisional, dalam pembangunannya sudah mengadopsi beberapa konsep kota kompak yang berkelanjutan dengan cara mereka sendiri dalam keberlangsungan dan pemeliharaan kampung sebagai kawasan heritage.